HUBUNGAN KETERSEDIAAN RAMBU-RAMBU PERPUSTAKAAN DENGAN TEMU KEMBALI INFORMASI - Inawati Inawati; Gita Sulika Sari (Jurusan Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2022)
This study aims to determine how big the relationship between the signs in the library and the speed of information retrieval at the Malang State University Library. This type of quantitative research with correlation analysis method. The population of all students of the 2019 State University of Malang with a sample of 100 students who use library services. The results of the study indicate that there is a moderate relationship between existing signs and information retrieval at the Malang State University Library as seen from the correlation coefficient value of 0.583 with a significance level of 0.000 which means that the application of signs in the Malang State University Library has a relationship with the speed in the retrieval of information that is used as a guide in searching for information.